TOOLS FOR CONCEPTUAL-ALGORITHMIC PROTOTYPING OF PROJECT SOLUTIONS IN SOFTWARE INTENSIVE SYSTEMS DESIGN - Obaid, Ali Hamzah; Obayes Al-Husseini, Khansaa Azeez (International Journal of Engineering Technologies and Management Research, 2018)
This article describes the development of a design tool that provides the ability to manage quickly create prototypes of design solutions, including graphical elements and software components that are connected together. At the same time, this tool should be universal and suitable for use in various projects.